2016
DOI: 10.1101/040642
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Balanced excitation and inhibition decorrelates visual feature representation in the mammalian inner retina

Abstract: The retina extracts visual features for transmission to the brain. Different types of bipolar cell split the photoreceptor input into parallel channels and provide the excitatory drive for downstream visual circuits. Anatomically, mouse bipolar cell types have been described down to the ultrastructural level, but a similarly deep understanding of their functional diversity is lacking. By imaging light-driven glutamate release from more than 11,000 bipolar cell axon terminals in the intact retina, we here show … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 102 publications
2
15
0
Order By: Relevance
“…This suggests that mechanisms responsible for the nonlinear behavior of the postsynaptic excitatory current are localized to the bipolar-ganglion cell synapses. Possible sources of such nonlinear behavior include presynaptic inhibition from amacrine cells, which can directly gate glutamate release from bipolar cell terminals (Eggers and Lukasiewicz, 2011; Euler et al, 2014; Franke et al, 2016; Schubert et al, 2008; Zaghloul et al, 2007), and synaptic depression at bipolar terminals caused by vesicle depletion (Jarsky et al, 2011; Markram et al, 1998; Ozuysal and Baccus, 2012).
10.7554/eLife.19460.006Figure 2.The divisive suppression (DivS) model of synaptic currents.( A ) Schematic of retinal circuitry.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggests that mechanisms responsible for the nonlinear behavior of the postsynaptic excitatory current are localized to the bipolar-ganglion cell synapses. Possible sources of such nonlinear behavior include presynaptic inhibition from amacrine cells, which can directly gate glutamate release from bipolar cell terminals (Eggers and Lukasiewicz, 2011; Euler et al, 2014; Franke et al, 2016; Schubert et al, 2008; Zaghloul et al, 2007), and synaptic depression at bipolar terminals caused by vesicle depletion (Jarsky et al, 2011; Markram et al, 1998; Ozuysal and Baccus, 2012).
10.7554/eLife.19460.006Figure 2.The divisive suppression (DivS) model of synaptic currents.( A ) Schematic of retinal circuitry.
…”
Section: Resultsmentioning
confidence: 99%
“…Although synaptic depression could also explain fast transient responses and contrast adaptation (Ozuysal and Baccus, 2012), synaptic depression will generally result in excitation and suppression that have the same spatial profiles (Figure 4—figure supplement 1 and 2), whereas we show that excitation and suppression have distinct spatial profiles (Figure 4). Therefore, the divisive suppression in our model likely depends partly on presynaptic inhibition from amacrine cells, which can extend their suppressive influence laterally (Euler et al, 2014; Franke et al, 2016; Schubert et al, 2008). This was somewhat surprising, because earlier studies had shown that contrast adaptation persisted in the presence of inhibitory receptor antagonists, suggesting that adaptation depended primarily on mechanisms intrinsic to the bipolar cell (e.g., synaptic depression), independent of synaptic inhibition (Beaudoin et al, 2007; Brown and Masland, 2001; Rieke, 2001).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1c). Indeed, this can be seen in direct recordings from bipolar cells [28,29,30], measurements of bipolar cell output [31,11] or in recordings of RGC excitatory input [32] (and see Fig. 2c,d).…”
Section: Introductionmentioning
confidence: 99%
“…First, nonlinear processing in the retina can contribute more to decorrelating retinal ganglion cell (RGC) responses to natural scenes than the RF surround [10] (see also [11,12]). Second, human fixational eye movements can remove spatial correlations in natural inputs before any neural processing takes place [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%